Functional bioactive compounds in ginger, turmeric, and garlic - Ajanaku, Christiana Oluwatoyin; Ademosun, Olabisi Theresa; Atohengbe, Prudence Osahenomanse; Ajayi, Samuel Oluwakayode; Obafemi, Yemisi Dorcas; Owolabi, Olayinka Ayotunde; Akinduti, Paul Akinniyi; Ajanaku, Kolawole Oluseyi (Frontiers in Nutrition, 2022)
Nutrition plays a very important role in individuals' health promotion and brought about a global paradigm shift from pharmaceuticals to nutraceuticals. This is due to the high cost, non-availability, and side effects associated with the unregulated consumption of pharmaceuticals. Over the ages, nutraceuticals from food products were reported to contain bioactive compounds with excellent health and physiological benefits. This report reviews bioactive compounds in selected foods namely; ginger (Zingiber officinale), turmeric (Curcuma lunga), and garlic (Allium sativum) as potential natural therapeutics for ailments of cancer and heart-related diseases. Analytical profile, functional activities and characterisation of these compounds were discussed with possible recommendations for prospective treatment of diseases using these nutraceuticals.